THE PREPARATION OF FUTURE TEACHERS OF PHYSICS TO REALIZATION OF THE INFORMATION FUNCTION - Ivanitsky О.І. (Journal of Information Technologies in Education (ITE), 2012)
The author considers the problems associated with the preparation of the future teachers of physics to the realization of the information function under conditions creation of informational and communication environment.